Efficiency and Contribution of Labor in Rice Farming in the Lower Bengawan Solo River Basin, Bojonegoro Regency - Probowati, Deviana Diah; Masahid, Masahid (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Agriculture contributes to development as an economic activity, as a livelihood and as a provider of environmental services. Farmers can be likened to companies because farmers, apart from being producers, are also workers and managers who manage rice farming so that optimal production results are obtained. Bojonegoro Regency is one of the districts that passes through the Bengawan Solo River. Most of the rice fields in Bojonegoro Regency have irrigation channels originating from the Bengawan Solo river. The farmer's household economy consists of production, consumption and labor contribution activities in farming. For rice farming activities, farmers need input including labor, both family labor and non-family labor. Labor in rice farming includes male labor and female labor, both family labor and non-family labor. The aim of this research is to analyze labor efficiency in the household economy of rice farmers in the Hilir Bengawan Solo watershed and to analyze the contribution of family labor to the income of rice farmer families. The research method uses a survey method by taking 30 samples. The analysis technique used uses the DEA analysis method and the contribution of labor to farming family income. The research results show that DEA is 0.35 and the contribution of labor to family income is 52.5%, which is considered moderate.